Perlindungan Hak Perempuan Di Iran Berdasarkan Instrumen Cedaw - Rachma Rizky Melania Latuconsina; Josina Augusthina Yvonne Wattimena; Arman Anwar (Faculty of Law Pattimura University, 2021)
Introduction: This research discusses the issue of women's rights that occur in Iran that requires deeper attention and protection, it is seen based on the CEDAW instrument that cases that occur in Iran violate the provisions of CEDAW. Purposes of the Research: Knowing and analyzing about the protection of women's rights under CEDAW in Iran.Methods of the Research: This study uses a normative juridical method with the legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: The results of the research show that violations of women's human rights in Iran still frequently occur, in the form of honor killings and so on. The efforts of national and international agencies such as CEDAW have still not been able to solve this problem because in fact many violations are still found in Iran.